Failure case studies of SA213-T22 steel tubes of boiler through computer simulations - Purbolaksono J.; Ahmad J.; Khinani A.; Ali A.A.; Rashid A.Z. (2023)
Increased temperature and decreased hardness values of the tube metal and development of oxide scale on the inner surface of boiler tubes over prolonged period of time are typical problems in power plants. Appropriate life assessments or condition monitoring of boiler tube should be carried out from time totime. Computer simulations may economically support the post-failure assessment method, i.e. visual inspections, metallurgical examinations and mechanical strength measurements. However, estimations obtained from the simulations may provide an advanced warning to take preventive actions prior to failure. In this work two failure cases of the reheater and superheater tubes made of a typical material of SA213-T22 steel are evaluated. As the oxide scales are increasingly developed on the inner surface, the increasing of temperature and decreasing of hardness value in tube metal for both cases are determined. The remnant life estimations are then made in the form of creep cumulative damages. 2009 Elsevier Ltd. All rights reserved.